Cerebral venous thrombosis is associated with major vessel disease in Behçet's syndrome. Issue 12 (16th November 2004) - Tunc, R; Saip, S; Siva, A; Yazici, H
Abstract : Objective: To examine the association between the type of central nervous system (CNS) involvement (parenchymal disease and cerebral venous thrombosis (CVT)) and extra-cranial large vessel events, mainly venous thrombosis, in Behçet's syndrome (BS). Methods: Conventional venous angiograms, Doppler ultrasonography, computed tomography, and MR angiography were used to study 88 patients with BS, with (n = 88) and without (n = 80) CNS disease for the presence of major vessel disease. Results: Major vessel involvement among the male patients with and without CNS disease (21/73 (29%) v 18/80 (23%), respectively) showed no significant differences (p = 0.374). When patients with CNS disease were stratified according to the type of CNS involvement, 7/11 (64%) patients with CVT had major vessel disease compared with 15/77 (19%) patients with parenchymal disease (p = 0.004). The mean (SD) age of onset of CVT (23.1 (8.8) years) among the male patients was significantly earlier than among the men with parenchymal disease (32.0 (7.5); p = 0.002). Conclusions: CVT in BS was strongly associated with peripheral major vessel disease and occurred earlier in the disease course than the parenchymal type of CNS disease. As superficial thrombophlebitis also occurs more frequently in patients with major vessel disease in BS, this may suggest a common pathogenic mechanism.